2016
DOI: 10.1098/rspb.2016.1970
|View full text |Cite
|
Sign up to set email alerts
|

Handicap principle implies emergence of dimorphic ornaments

Abstract: Species spanning the animal kingdom have evolved extravagant and costly ornaments to attract mating partners. Zahavi's handicap principle offers an elegant explanation for this: ornaments signal individual quality, and must be costly to ensure honest signalling, making mate selection more efficient. Here, we incorporate the assumptions of the handicap principle into a mathematical model and show that they are sufficient to explain the heretofore puzzling observation of bimodally distributed ornament sizes in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…The selective maintenance of such male dimorphisms has been difficult to understand ( Simpson et al., 2011 ). Yet, a recent paper by Clifton et al (2016) concluded the evolution of male dimorphisms can be explained solely by the handicap principle ( Zahavi, 1975 ). It is not intuitively obvious how the handicap principle can selectively maintain male dimorphisms, and no verbal explanations were provided.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The selective maintenance of such male dimorphisms has been difficult to understand ( Simpson et al., 2011 ). Yet, a recent paper by Clifton et al (2016) concluded the evolution of male dimorphisms can be explained solely by the handicap principle ( Zahavi, 1975 ). It is not intuitively obvious how the handicap principle can selectively maintain male dimorphisms, and no verbal explanations were provided.…”
mentioning
confidence: 99%
“…
Figure 1 Fitness curves with three different benefit functions (concave, linear and convex respectively). The cost function is the same as that in Clifton et al. (2016) with Grafen's handicap conditions.
…”
mentioning
confidence: 99%
See 3 more Smart Citations